Answer: This equation has one solution.
Steps:
2+4(3-4x) = 5x +9
First, we need to distribute to the terms inside the parentheses.
4 * 3 = 12 and 4 * -4= -16x
Our equation now looks like this:
2 + 12 - 16x = 5x + 9
We can now combine like terms. We have 2 like terms that we can combine:
2 + 12 + = 14
Our equation now looks like this:
-16x + 14 = 5x + 9
We can now use inverse operations to get rid of 5x. The inverse operation for addition is subtraction; so we subtract 5x on both sides. Remember, our goal is to isolate the x.
-16x + 14 = 5x + 9
-5x -5x
The fives cancel out. Our equation now looks like this:
-21x + 14 = 9
We can now use inverse operations to get rid of the 14:
-21x + 14 = 9
- 14 -14
The fourteens cancel out. Our equation now looks like this:
-21x = -5
Last step! Now we use inverse operations to isolate the x. -21 is being multiplied by x; the inverse operation for multiplication is division.
-21x/-21 = and -5/-21 = 5/21
x is equal to 5/21.
Hope this helps!